2007
DOI: 10.1093/cercor/bhm190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Experience on Vascular Endothelial Growth Factor Expression during the Postnatal Development of the Rat Visual Cortex

Abstract: The development of the cortical vascular network depends on functional maturation. External inputs are an essential requirement in the modeling of the visual cortex, mainly during the critical period, when the functional and structural properties of visual cortical neurons are particularly susceptible to alterations. Vascular endothelial growth factor (VEGF) is the major angiogenic factor, a key signal in the induction of vessel growth. Our study focused on the role of visual stimuli on the development of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 55 publications
3
43
0
1
Order By: Relevance
“…As we reported previously (Bengoetxea et al, 2008), the increase in vascular density during the critical period of the visual cortex runs parallel to the increase of VEGF levels. Our results show that although the infusion of VEGF does not reach control values, it is still significantly higher than in anti-VEGF-infused animals, this trend being similar to the trend in vascular or neuronal density quantifications.…”
Section: Vegf Levelssupporting
confidence: 85%
See 3 more Smart Citations
“…As we reported previously (Bengoetxea et al, 2008), the increase in vascular density during the critical period of the visual cortex runs parallel to the increase of VEGF levels. Our results show that although the infusion of VEGF does not reach control values, it is still significantly higher than in anti-VEGF-infused animals, this trend being similar to the trend in vascular or neuronal density quantifications.…”
Section: Vegf Levelssupporting
confidence: 85%
“…Our previous results suggest that the increase of experience induces an increase in vascular density mediated by a peak in the secretion of VEGF. This peak occurs at the 4th postnatal week, shortly after the end of the minipump placement (Bengoetxea et al, 2008). The implantation-produced lesion induces a significantly lower increase of vascular density, which is one of the changes related to the postnatal maturation of the visual cortex (Argandoñ a and Lafuente, 1996Lafuente, , 2000Lafuente, , 2002Argandoñ a et al, 2005;Bengoetxea et al, 2008).…”
Section: Vascular Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas initial studies showed that EE modified cortical weight [20,21], subsequent studies described an increase of nuclear and soma size in neurons, dendritic branching or synapsis size [22][23][24] among other effects. Moreover, EE also increases neurogenesis in the hippocampus [13] as it increases the expression of angioglioneurins such as VEGF or BDNF [25][26][27]. Therefore, EE has strong effects on the plasticity of neural connections, especially in the visual cortex [28].…”
Section: Introductionmentioning
confidence: 99%